Increasing Student Learning Interest through Cooperative Learning - Sulfiani, Besse; Nurhayati, Nurhayati; Abdullah, Erviana; Takwa, Eka Setia; Fitriani, Fitriani; Nesti, Vera Ayu (Journal La Edusci, 2024)
This study aims to explain the influence of cooperative learning on the increase in students' interest in learning in the context of education. A qualitative approach with the type of library research is used to explore the concept of cooperative learning and its impact on students' interest in learning. Through secondary data analysis and using Miles and Huberman data analysis methods, this study gained an in-depth understanding of how cooperative learning affects students' learning interests. The results of the study show that the application of the cooperative learning model results in a significant increase in students' interest in learning. Factors such as the integration of game elements, cooperation between students in teams, and an inclusive environment play a key role in stimulating greater interest in learning. Cooperative learning strategies not only improve academic achievement, but also create high motivation for students to understand the learning material better. Nonetheless, challenges such as an unsupportive environment and active student involvement need to be addressed through a precise and sustainable approach that involves collaboration between educators, students, and education stakeholders.